The influence of soccer playing actions on the recovery kinetics after a soccer match - Nedelec, M.; McCall, A.; Carling, C.; Legall, F.; Berthoin, S.; Dupont, G. (The Journal of Strength and Conditioning Research, 2014)
This study examined the relationship between the frequency of playing actions performed during a soccer match and the recovery kinetics after the match. Time motion analyses were performed on 10 professional soccer players during 4 competitive matches (14 observations) to determine the number of playing actions completed by players. Subjective ratings, creatine kinase, and physical tests (countermovement jump [CMJ], isometric maximum voluntary contraction of the hamstrings, 6-second sprint on a nonmotorized treadmill) were performed before the match and 24 hours, 48 hours, and 72 hours after the match. During the 72-hour recovery period, CMJ, isometric strength of the hamstring muscles, and peak sprint speed significantly (p < 0.05) decreased, whereas muscle soreness increased (p < 0.05). Significant correlations were observed between the increase in muscle soreness and number of short sprints (<5 m) performed at 48 hours (r = 0.74; confidence interval [CI], 0.35-0.91; p < 0.01) and 72 hours (r = 0.57; CI, 0.05-0.84; p < 0.05) after match play. A significant relationship (r = -0.55; CI, -0.84 to -0.03; p < 0.05) was also observed between CMJ performance decrement at 24 hours and the number of hard changes in direction performed. Soccer match play resulted in significant neuromuscular fatigue for up to 72 hours after match and was dependent on the number of sprints and hard changes in direction performed during the match. Time motion analysis data currently used during a soccer match should quantify hard changes in direction, acceleration and deceleration phases to enable better estimations of postmatch fatigue.